Reconstructing global governance networks: the case of the OECD test guidelines programme for the testing of chemicals - Martin Herberg (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
Using qualitative-sociological research methodology, the article explores the phenomenon of standard-setting by transnational administrative networks. Regarding both the enormous problem-solving capacity and the occurring threats for legitimacy, it is examined whether such network-like arrangements are capable of creating their own institutional safeguards and internal mechanisms of control and accountability. As an empirical case for a more detailed reconstruction, the OECD Test Guidelines Programme for the Testing of Chemicals was chosen. As will be argued, the initiative is an almost paradigmatic example for the emergence of specific checks and balances, and the institutionalization of principles such as fairness and impartiality in a sphere beyond the constitutional state. – – Der Aufsatz widmet sich dem Phänomen der Standardsetzung durch globale Verwaltungsnetzwerke und benutzt hierbei Methoden und Konzepte der qualitativ-soziologischen Netzwerkanalyse. Transnationale Verwaltungsnetzwerke verfügen oft über ein erstaunliches Problemlösungspotential, gleichzeitig werfen sie aber spezielle Legitimationsprobleme auf. Zu erörtern ist die Fähigkeit von Netzwerken, diese Probleme zu erkennen und zu ihrer Lösung geeignete institutionelle Schutz- und Kontrollmechanismen zu etablieren. Als Untersuchungsfall für eine genauere empirische Rekonstruktion wurde das OECD Prüfrichtlinienprogramm für das Testen von Chemikalien gewählt. Anhand der Initiative lässt sich gut veranschaulichen, dass rechtsstaatliche Prinzipien wie Unparteilichkeit, Fairness und Gewaltenteilung grundsätzlich auch in einer Sphäre jenseits des Nationalstaats etabliert werden können.
Keywords: 300; Chemikalienrecht; Normung; Netzwerk; Global Governance; OECD-Staaten